2009
DOI: 10.1242/jeb.037275
|View full text |Cite
|
Sign up to set email alerts
|

Distinct freshwater and seawater isoforms of Na+/K+-ATPase in gill chloride cells of Atlantic salmon

Abstract: SUMMARYGill Na + /K + -ATPase (NKA) in teleost fishes is involved in ion regulation in both freshwater and seawater. We have developed and validated rabbit polyclonal antibodies specific to the NKA 1a and 1b protein isoforms of Atlantic salmon (Salmo salar Linnaeus), and used western blots and immunohistochemistry to characterize their size, abundance and localization. The relative molecular mass of NKA 1a is slightly less than that for NKA 1b. The abundance of gill NKA 1a was high in freshwater and becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
104
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(130 citation statements)
references
References 33 publications
14
104
0
Order By: Relevance
“…Future work should assess whether one or more Fxyd isoforms are co-localized with Na C , K C -ATPase a subunits in tilapia gill. The changes in a-1a and a-1b isoforms observed in tilapia after FW and SW transition in this study largely mirror previous reports in rainbow trout (Richards et al 2003), Arctic char (Bystriansky et al 2006) and Atlantic salmon , McCormick et al 2009). The marked elevation in a-1a expression after FW transition (60-fold) and a-1b expression after SW transition (tenfold) observed in this study is of a greater magnitude than that reported in the salmonid fishes described earlier.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Future work should assess whether one or more Fxyd isoforms are co-localized with Na C , K C -ATPase a subunits in tilapia gill. The changes in a-1a and a-1b isoforms observed in tilapia after FW and SW transition in this study largely mirror previous reports in rainbow trout (Richards et al 2003), Arctic char (Bystriansky et al 2006) and Atlantic salmon , McCormick et al 2009). The marked elevation in a-1a expression after FW transition (60-fold) and a-1b expression after SW transition (tenfold) observed in this study is of a greater magnitude than that reported in the salmonid fishes described earlier.…”
Section: Discussionsupporting
confidence: 91%
“…The discovery of two Na C , K C -ATPase a-1 isoforms in the gill of salmonids, a-1a, expressed mainly in FW, and a-1b, expressed mainly in SW, provided important insight into transepithelial ion transport in the gill. In every salmonid species examined to date, salinity acclimation induces a reciprocal switch between a-1a and a-1b isoforms, a-1a being prominent in FW and a-1b in SW (Richards et al 2003, Mackie et al 2005, Bystriansky et al 2006, McCormick et al 2009), suggesting that a-1a is an FW isoform involved specifically in ion uptake, whereas a-1b is an SW isoform associated with ion excretion. Whether this phenomenon is restricted to the early salmonid branch of the teleost clade or is a more general prerequisite for euryhalinity is unknown.…”
mentioning
confidence: 99%
“…NKA provides the driving force for ion transport within ionocytes. In salmon, NKAα1a expression is higher in FW than in SW and NKAα1b expression is higher in SW than in FW (Madsen et al, 2009;McCormick et al, 2009). This pattern of salinity-dependent NKA isoform expression was also described in tilapia .…”
Section: Discussionmentioning
confidence: 97%
“…The electrochemical gradient that drives transmembrane ion transport is provided by the basolaterally located ion pump, Na + /K + -ATPase (NKA) (Richards et al, 2003). In tilapia, salmonids and killifish, two isoforms of NKA, α1a and α1b, are differentially expressed in the gill, according to the salinity of the habitat (Richards et al, 2003;Madsen et al, 2009;McCormick et al, 2009;Tipsmark et al, 2011;Berdan and Fuller, 2012). In tilapia, NKAα1a expression predominates in FW-acclimated fish relative to SW-acclimated fish, while NKAα1b expression has been shown to be greater or unchanged in SW-acclimated fish when compared with FW-acclimated fish .…”
Section: Introductionmentioning
confidence: 99%
“…These studies show an increase and then recovery in plasma sodium and chloride levels, coinciding with an increase in gill Na (Hoar, 1988). The observed changes in gill Na + /K + -ATPase expression involve switching between two distinct isoforms of this protein, as mRNA (Richards et al, 2003;Bystriansky et al, 2006) and protein (McCormick et al, 2009) expression of the 1b isoform increases during seawater acclimation, while expression of the 1a isoform decreases during the transition to seawater. In contrast, very few studies have examined the physiology of the gill during acclimation of salmonid fishes to freshwater.…”
Section: Introductionmentioning
confidence: 89%